Sequencing analysis of HPV-other type on an HPV DNA chip - Min-Jeong Kim; Jin Ju Kim; Sunmie Kim (Korean Society of Obstetrics and Gynecology, 2018)
ObjectivesTo identify the specific human papillomavirus (HPV) genotypes from HPV-other type on an HPV DNA chip test by sequencing.MethodsAmong 13,600 women undergoing a routine gynecology examination including Pap smear and/or HPV test by DNA chip test in the healthcare system at Gangnam Center from July 2012 to February 2013, we prospectively collected and performed sequencing for a total of 351 consecutive cervicovaginal samples consisting of 180 samples that tested positive for HPV-other type and 171 samples that tested positive for either high-risk HPV or low-risk HPV.ResultsOf a total of 351 samples, individual HPV genotypes were successfully sequenced in 215 cases: 119 HPV-other type, 82 HPV-high-risk, and 14 HPV-low-risk. Based on the sequencing for 119 HPV-other type samples, 91.6% were detected as HPV types that were not included on the DNA chip; however, 7.6% (9/119) were proven to be high-risk HPV types: HPV 18 (n=4), HPV 33 (n=3), HPV 35 (n=1), and HPV 59 (n=1). For correlation analysis of all high-risk and HPV 16/18, the correlation rate was 76.2% and 86.6% with kappa-value of 0.38 and 0.69, respectively.ConclusionHPV-other type on DNA chip test may still have possibility of high-risk HPV, i.e., HPV 18 and thus the significance of HPV-other type in detecting cervical disease remains to be investigated.